EFFECTS OF EXPOSURE TO MICROWAVE RADIATION AND NARROWBAND LASER ON THE REGENERATION OF MERISTEMATIC EXPLANTS OF POTATO - Bekseitov , T.K.; Anikinа , I.N.; Dzhaksybaeva , G.G.; Seytzhanova , D.D. (Eurasian Journal of Applied Biotechnology, 2015)
Virus-free seed potato are used worldwide as meristems. The limitation in the implementation of this method in practice is the very small size of the virus-free zone of the meristem, which is often located within 0.05 mm, and meristematic explants of such sizes are characterized by a weak capacity for regeneration that is considerably difficult to obtain in first tube-plants. For efficiency, apical meristems are used as chemical stimulating factors, and physical factors increase the regenerative capacity of meristems. In this study, we first investigated the possibility of the use of potato meristems complex explants for the stimulation of the regenerative capacity with microwave irradiation-selected rays and narrowband lasers. For irradiation, a high-frequency signal generator with a frequency range of 37.5–53.57 GHz. The microwave power was 20 mW. As a result, the following data were obtained: irradiation with microwave beams and narrowband lasers for 60 min and 80 min on medium meristems promoted the accelerated passage of the phases of development, increased size characteristics, reduced death due to tissue necrosis, and thus increased their regenerative capacity. This method significantly increased the effectiveness of the technology of the source of virus-free seed potatoes.